PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI PENAMPUNGAN AIR MINUM TARA WATER DESA SIDOJADIKECAMATAN BUKIT MALINTANG KABUPATEN MANDAILING NATAL - Eka Anugrah; Arwin Arwin; Mufti Fahrizal (Adisam Publisher, 2025)
This research aims to determine the effect of service quality on consumer satisfaction at the Tara Water water depot, Sidojadi Village, Bukit Malintang District, Mandailing Natal Regency. The sample used was 100 respondents using the Accidental Sampling method. By using a simple linear regression analysis method. The research results show that service quality has a positive and significant effect on consumer satisfaction with a significance value of 0.000<0.05. The resulting coefficient of determination is 0.522, which means that 52.2% of changes in the consumer satisfaction variable are explained by changes in the service quality variable, while the remaining 47.8% is explained by other variables not included in this research.